OPEN MUSEUM AS A TOOL FOR CULTURE SUSTAINABILITY: PRAMBANAN TEMPLE STUDY CASE - Munadjat Wardoyo; Rilla Oktoviami Zef (Universitas Padjadjaran, 2020)
The rapid city developments are certainly through planning which will affect the development directly or indirectly. So it is very important to take care of historical buildings or other cultural heritage. A cultural heritage is certainly a major attraction of heritage tourism in a city that has historical heritage. In this discussion it was also stated that the open museum is an effective tool for maintaining urban heritage, preserving history and culture, and encouraging sustainable tourism in an area that relies on heritgae tourism in urban areas. Prambanan Temple is one of the cultural heritage areas included in the UNESCO world heritage site list, located in urban areas and vulnerable to changes both in terms of rapid urban development. This study uses a non-interactive qualitative method, namely by analyzing through existing documents. In addition, this research was also supported by literature review related to the open museum in the city of Mecca which could be used as a guide for application to further strengthen the sustainability of Prambanan Temple from the impact of urban development and the development of heritage toursim. Literature on urban heritage tourism, cultural heritage sites, and sustainable development is a support in understanding the urgency of research issues and drawing conclusions to plan the Prambanan Temple as an Open Musuem. Open museums do not just become a label but also apply certain conditions so that the building of cultural heritage can continue to be maintained its authenticity in line with urban development and heritage tourism.